2 - Songs of the King’s Wives: Women, Power and Performance in the Yoruba Public Sphere: https://doi.org/10.4314/ad.v34i2.57365 - Omojola, Bode (Africa Development, 2009)
Indigenous festivals, which rely significantly on music and dance, often constitute the village public sphere and the social arena within which the structures of power are performed and negotiated in tradi- tional African communities. This article discusses two unique musical traditions which feature prominently at annual traditional festivals in Emure-Ekiti, a Yoruba town in Western Nigeria. The musical traditions are orin olori (songs of the king’s wives) and a related ensemble, orin airegbe, a musical tradition associated with female chiefs. Exploring an ethnomusicological approach, this article argues that the complemen- tary relationship between these two all-female musical traditions and the scope of their performance practices draw attention to the ways in which public performance sp aks to the status and agency of women in traditional Yoruba societies.